Ureteral Hemangioma: a clinical case report - Maestroni, U.; Dinale, F.; Frattini, et al., A. (Acta Biomedica Atenei Parmensis, 2005)
The most greater part of the tumors ureteralis are of malignant nature, they are verified especially in the elderly patient and they have a preference for the distal third of the ureter. Of the tumors benign ureteral, the emangioma is a very rare vascular neoplasm. The symptoms aspecificis of presentation are: hematuria, colic type pains, hydronephrosis and bladder inflammation. Thanks to the refinement of the radiological techniques (Urography, CTscan and eventually the ascending pyelography) and also to the simultaneous aid of the anatomopathologist, it is possible to obtain an accurate description of this pathology in a precocious stage in order to carry out a conservative approach. The peculiarity of the clinical case from us described depends on the fact that it deals with an occasional find, reaches our observation for appearance of severe hydronephrosis caused by ureteral stones, resolved him with methodic endoscopic.